Eco-friendly Computing and Communication Systems International Conference, ICECCS 2012, Kochi, India, August 9-11, 2012. Proceedings - Mathew, Jimson; Patra, Priyadarshan; Pradhan, Dhiraj K.; Kuttyamma, A. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International Conference Eco-friendly Computing and Communication Systems, ICECCS 2012, held in Kochi, Kerala, India, in August 2012. The 50 revised full papers presented were carefully reviewed and selected from 133 submissions. The papers are organized in topical sections on energy efficient software system and applications; wireless communication systems; green energy technologies; image and signal processing; bioinformatics and emerging technologies; secure and reliable systems; mathematical modeling and scientific computing; pervasive computing and applications.
Energy efficient software system and applications -- Wireless communication systems; green energy technologies -- Image and signal processing -- Bioinformatics and emerging technologies -- Secure and reliable systems -- Mathematical modeling and scientific computing -- Pervasive computing and applications.
Keywords: Computer science; Computer communication systems; Data encryption (Computer science).; Artificial intelligence; Computer simulation; Image processing; Bioinformatics; Computer Science; Image Processing and Computer Vision; Computational Biology/Bioinformatics.; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Data Encryption; Simulation and Modeling; Electronic books